Biopolymer‐based antimicrobial coatings for aquatic food products: A review. Issue 4 (15th February 2022) - Chakraborty, Priyanka; Nath, Debarshi; Hoque, Monjurul; Sarkar, Preetam; Hati, Subrota; Mishra, Birendra Kumar
Abstract: Aquatic food products, including fish and crustaceans, are some of the most consumed foods globally and are highly prone to microbial contamination. Such products have been preserved using conventional processing techniques such as freezing, cold storage, modified atmospheric packaging (MAP), and vacuum packaging. However, these techniques have been used since decades and are not cost‐effective. Therefore, alternative sustainable strategies need to be explored. One viable option is the application of biopolymer‐based films and coatings loaded with active antimicrobial agents (peptides and essential oil components) for the preservation of aquatic food products. Nisin is the most widely used peptide for the development of antimicrobial coatings, while eugenol, carvacrol, and cinnamaldehyde are among the most popular essential oil compounds. Findings reveal that both peptides and essential oils, when applied in combination within a coating system, demonstrate robust antimicrobial activity, delayed lipid oxidation, and retain the overall quality of the aquatic food system. Novelty impact statement: Antimicrobial‐based coating systems have recently gained worldwide attention due to their ability to delay food contamination and maintain product quality throughout the storage period. This review provides a comprehensive description of peptide and essential oil‐loaded coating systems and their application in the shelf‐life extension of aquatic food products. In addition, the application of nanocomposite systems for the preservation of aquatic foods has been discussed.